Infection of Transmissible Gastroenteritis Virus in Pig - Indrawati Sendow (Media Veteriner, 1998)
TransmissIble gastroenteritis (TGE) virus belong to corona virus which cause acute diarrhoea in under two years old young pig, especially young piglets. The pigs experience severe loss of body fluid which can lead to death. To prevent the disease, vaccination is a must, but the vaccine available at present is not effective. It is quite difficult to diagnose TGE clinically and diarrhoea could be due to other agents, i.e. bacterial, parasite and another viral infections. A comprehensive conclusion of laboratory examination, pathological finding, and clinical signs in the field can lead to definitive diagnose of TGE. A review about the disease, causative agent, characteristic of the agent, clinical signs, epidemiology, diagnose, control and prevention, and the occurrence in Indonesia based on serological result is presented.